Some sing, some cry - Shange, Ntozake; Bayeza, Ifa (New York St. Martin's Press, 2010)
The story of emancipated slave Elizabeth Mayfield traces her rise as the matriarch of a family of musically gifted Southern women who overcome brutal obstacles while witnessing key moments in American history
Includes bibliographical references (p. [563]-564)
1
Keywords: African American families -- Fiction; Epic fiction; Historical fiction